Conceptual Framework: Determinant Factors For Paying Zakat Fitrah Via Fintech - Aman Shah Siraj; Mohd Faisol Ibrahim; Nuradli Ridzwan Shah Mohd Dali (Universiti Sains Islam Malaysia, 2024)
VOL.19 NO. 2 2022 Page (102-124)